Identification, isolation and pathogenicity of Aeromonas salmonicida and his-topathology of infected Oncorhynchus mykiss in Punjab and northern areas of Pakistan - Muhammad Akram; Muhammad Hafeez-ur-Rehman; Farzana Abbas; Imran Altaf; Sidra Kanwal; Nimra Mobeen; Aiza Khaliq; Asma Sharif; Maria Tayyaba; Saira Talib; Muhammad Nouman Riaz; Saima Zafar; et al. (Journal of Fisheries)
Aeromonas salmonicida causes furunculosis in the Oncorhynchus mykiss (rainbow trout) and the effective control over this infection requires knowledge of the genetic variability and epidemiology of A. salmonicida. Pathogenic strains were isolated from kidneys, muscles, liver and spleen of rainbow trout from the provinces, Punjab, Khyber Pakhtunkhwa and Gilgit Baltistan, Pakistan. On the base of 16S rRNA sequencing, physiological and biochemical characterization, isolated bacterial strains were identified as A. salmonicida (NCBI Ref. ArS-Pak-19 [MW307221], ArS-Pak- GB1-19 [MW720959], ArS-Pak-MRE-19 [MW720960], ArS-Pak-SW2-19 [MW720961], ArS-SW1-Pak-19 [MW720962]). Isolated strains were resistant to antibiotics like sulfamethoxazole, penicillin, vanomycine, rifampicin and bacitracin but were extremely sensitive to spectinomycin, ciprofloxacin, ofloxacin, levofloxacin and nalidixic acid. To check out the pathogenicity, rainbow trout were experimentally infected with isolated strains. Experimental fishes showed the same symptoms as were recorded in naturally infected fish including jaw bleeding, intra-abdominal fluid, intestinal bleeding and gill filament anemia. After ten days of post-challenge study, histopathological analysis revealed that there were severe alterations in the spleen, liver and kidney of the infected fish. The present study provides further research foundation and for upcoming research on A. salmonicida disease, its control and epidemiology.